Politics Then and Now: Introduction - Barringer, Richard; Palmer, Kenneth (Maine Policy Review, 2014)
This article is an introduction to several articles and excerpts published in this issue of Maine Policy Review based on a series of related lectures. One set of lectures, “Politics Then and Now, in Maine and the Nation,” was presented by the Muskie School and Osher Lifelong Learning Institute at the University of Southern Maine in the fall of 2013, and the other was the William S. Cohen lecture held at the University of Maine. Most of the speakers are prominent public office holders who were asked to address the issue of political polarization and dysfunction, comparing how politics was played in the past with the current situation, and discussing what Maine can offer based on experiences here. Series organizers Richard Barringer and Ken Palmer provide an overview of the lectures and a summary of some of the common themes.